Effects of sowing densities on peanut production - Nakagawa, João; Lasca, Dalmo de Campo; Neves, João Paulo de Souza; Neves, Gessy de Souza; Sanches, Sérgio Veraguas; Barbosa, Valmir; da Silva, Maurício Nunes; Rossetto, Cláudia A. V. (Pesquisa Agropecuaria Brasileira, 1994)
In this work, the effects of sowing densities on peanut (Arachis hypogaea L.) crop, cv. Tatu were studied. Three experiments were carried out under field conditions on a soil classified as "Latosol Roxo", in the Municipality of Pontal, SP, during the wet seasons of 1987-88, 1988-89, and 1989-90. The densities studied were 7, 10, 13, 16, 19, 22, 25, and 28 seeds in one meter of row, under some row spacing of 0.60 m. The pod number per plant was the yield component responsible for the variation of pod production per plant and these decreased with the increase of sowing density. However, the low pod production per plant in high densities of sowing was compensated by the high populations of plants and these produced high yield. Thus, good pod yields were obtained, without significant losses of yield compared with the higher densities, at density of 13 seeds per meter, in 1987-88, 16 seeds per meter in 1988-89 and 10 seeds per meter in 1989-90, that resulted, respectively, in 1 1.36, 12.72 and 9.28 plants per meter at harvest time.